Use of CORE-OM as a benchmarking tool for patient outcomes at Counselling Psychology Units in Malaysian government hospitals / Norainee Kamaruddin - Norainee , Kamaruddin (2020)
The study aimed to use an alternative method of assessing client outcomes, and service performance by using the outcome measure—Clinical Outcomes in Routine Evaluation (CORE-OM). Presently, the counselling psychology unit assesses the clients' outcomes by subjective observations and clients' self-reports. As for service performance, the counselling psychology units are assessed internally by each hospital's management system. In advanced countries, these methods have been replaced or augmented by standardised routine outcome measures. This study used CORE-OM to measure client outcomes, and it was also the benchmarking tool to set service performance standards. It adopted a mixed-method research design using survey and interview as data collection methods. The survey participants were clients from 13 counselling psychology units in selected government hospitals around the country, and the interview participants were the psychology officers (counselling). The data collection methodology had two phases. The first phase entailed the collection of pre- and post-CORE-OM questionnaires from 103 clients and the second phase, involved a semi-structured interview with three psychology officers (counselling). The findings showed that 9% of clients recovered, 66% of clients improved, 16% of clients showed no-change, and 10% of clients had deteriorated. The benchmarking tool—CORE-OM—had determined the service standards of each outcome category. Based on the benchmarking values, one unit achieved the standard for all outcome categories, while the rest showed average performances. The interviews revealed themes on unit evaluation, workforce needs, outcomes concept misunderstood, inappropriate tools, challenging counselling process and low mental health campaigns. These themes had impacted the quantitative findings, and they shed light on the interactions between the variables, which led to the counselling psychology units' average performance. The study has implications for theory, practice, training, and future research. The study hoped that the Ministry of Health would consider implementing CORE-OM for assessing client outcomes and as a benchmarking tool for assessing service performance.